DEVELOPMENT OF TECHNICAL DOCUMENTS IN THE QUALITY MANAGEMENT SYSTEM” (CIPEEX, 2025)
Introduction: Standard Operating Procedures (SOPs) are essential technical documents for ensuring quality in healthcare services, as well as in laboratory, pharmaceutical, and industrial settings. They guarantee the standardization of activities, promoting safety, traceability, and compliance with regulatory standards. The proper development and implementation of these documents directly impact process effectiveness and the minimization of operational errors.Objective: To conduct a review on the importance of developing SOPs in the context of quality management.Methodology: Articles published between 2015 and 2025, in Portuguese and English, addressing the development, implementation, or impact of SOPs on service quality were included. The search was carried out in September 2025 in the BVS, SCIELO, and PubMed databases. The descriptors used were: “standard operating procedures” OR “technical documentation” AND “quality management.”Results: The analyzed studies demonstrated that the effective use of SOPs significantly contributes to continuous process improvement, supports internal and external audits, strengthens the quality culture, and reduces variability in performed activities. In addition, SOPs are indispensable tools for team training and ensuring regulatory compliance.Conclusion: Proper development of SOPs is essential for quality management, serving as an instrument that promotes standardization, safety, and continuous improvement. Professional training and constant document updating are key factors for the successful implementation of SOPs in any institution.
Keywords: Standard Operating Procedure; Technical Documentation; Quality Management